5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
-2a plus 3b
The given expression can be simplified to: 3b-a
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
Gathering like terms together, this is equal to 5a + 3b + 7c.
a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100
2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1
It is: 2a+5a = 7a when simplified
= a + b - 2
From your description, I get: a + b + c = 180b - 3a c = 5a You have two equations and three unknowns, which is unsolvable.